Improper charges in bank contracts: analysis of the financial impacts on consumers - Gomes, Cailane Máximo; Borges, Liliane de Moura (JRG Journal of Academic Studies, 2024)
This article seeks to reflect on undue charges in banking contracts, highlighting their financial impacts on consumers. From a bibliographical review, it is discussed how financial institutions, when implementing interest or services not foreseen or authorized in banking contracts, compromise, in addition to financial instability, emotional and psychological problems. The study addresses the historical evolution of consumer law, the way in which undue charges occur in banking contracts, as well as the losses caused to consumers. From this study, it was possible to verify the need for greater transparency on the part of banking institutions, highlighting the importance of stricter supervision and regulations on the part of consumer defense and protection bodies, to prevent such abuses and ensure a more balanced financial environment., fair and safe.